Nutrient demand for vegetation and fruiting of Coffea arabica L. - Souza, Laís Teles de (2018)
Coffee (Coffea arabica L.) nutrient demand depends on fruit load and intensity of the annual variation of vegetative growth. However, nutrient rates recommended for this crop are based only on bean yield, manily yields of old crops. Therefore, this research aimed to determine the source-sink relationship, through the effect of fruit load on vegetative growth, to understand coffee nutritional demand. The hypotheses were (i) the annual biomass of stem, branches and leaves should have a strong negative linear relationship regarding fruit load, (ii) the average nutrients concentration changes in the vegetative plant part due to the number of fruits, and (iii) the plant nutrient demand varies in years of high and low production due to the different proportions between fruiting and annual vegetation. The study was carried out from November 2015 to June 2016 in coffee trees in the municipality of Jacuí - MG, Brazil. The experimental design was completely randomized with one factor (fruit load), six factor levels (100%, 80%, 60%, 40%, 20% and 0%) and five replicates. After flowering, in early November 2015, six fruit loads were manually imposed and the base of the last pair of fully expanded leaf was labeled with wire on all branches of the trees. In early June 2016, during the coffee harvest, branches were cut from the wire-label and characterized. The variables analyzed were: numbers of nodes, leaf area, dry vegetation yield, dry bean yield, volume of fruits and concentration of macro and micro nutrients in vegetation and fruiting. The study revealed that fruit load strongly affects vegetative growth in Coffee arabica L. For each liter of fruit produced, ~ 103 g of dry vegetation yield decreases per tree. Furthermore, the concentration of the macronutrients N, P, K, Mg and S and the micronutrients Mn, Fe, Cu and Zn in vegetation and fruiting not dependent on fruit load. Nutrient demand of a given plant density varies in years of high and low production due to the different yield proportions of mass between fruiting and annual vegetation.